Rheological aspects of multilayer materials - Artemchuk, V. V. (Science and Transport Progress, 2011)
The issues related to renewal of worn-out parts of a rolling stock with the layered coatings are considered in the article. In developing a mathematical model of wearing a multilayer material as an object of rheology certain assumptions, which enable using the methods of mechanics and mechanics of continuous medium, are done.